ALUMINIAN LOW-CA PYROXENE IN A CA-AL-RICH CHONDRULE FROM THE SEMARKONA METEORITE - Rubin A.E. (My University, 2004)
A Ca-Al-rich chondrule (labeled G7) from the Semarkona LL3.0 ordinary chondrite (OC) consists of 73 vol% glassy mesostasis. 22 vol% skeletal forsterite, 3 vol% fassaite (i.e., Al-Ti diopside), and 2 vol% Al-rich, low-Ca pyroxene. The latter phase, which contains up to 16.3 wt% Al2O3, is among the most Al-rich, low-Ca pyroxene grains ever reported. It is inferred that 20% of the tetrahedral sites and 13% of the octahedral sites in this grain are occupied by Al. Approximately parallel optical extinction implies that the Al-rich, low-Ca pyroxene grains are probably orthorhombic, consistent with literature data that show that Al2O3 stabilizes the orthoenstatite structure relative to protoenstatite at low pressure. The order of crystallization in the chondrule was forsterite, Al-rich low-Ca pyroxene, and fassaite; the residual liquid vitrified during chondrule quenching. Phase relationships indicate that, for a G7-composition liquid at equilibrium, spinel and anorthite should crystallize early and orthopyroxene should not crystallize at all. The presence of Al-rich orthopyroxene in G7 is due mainly to the kinetic failure of anorthite to crystallize: this failure was caused by quenching of the G7 precursor droplet. Aluminum preferentially enters the relatively large B tetrahedra of orthopyroxene; because only one tetrahedral size occurs in fassaite, this phase contains higher mean concentrations of Al2O3 than the Al-rich orthopyroxene (17.8 and 14.7 wt%. respectively). Chondrule G7 may have formed by remelting an amoeboid olivine inclusion that entered the OC region of the solar nebula during an episode of chondrule formation.
Keywords: chondrite